28 Review of Operative and Non-Operative Time-Use During General Anaesthetic Cases in a Busy Surgical Oncology Service. (28th February 2022) - Bell, A.; Razzaq, Z.; Mustafa, H.; Redmond, H.P.
Abstract: Aim: To review theatre running times of all general anaesthetic cases performed in a single theatre during a set six-week period. We intend to assess the division of theatre time between operative and non-operative tasks and review areas of improvement in our department. Method: The data was collected concurrently by a member of the surgical team (AB) at the time of surgery. Date, surgical procedure, and time elapsed from knife-to-skin (KTS) to skin closure were monitored between the hours 08:30–17:00. Results were reviewed and presented graphically using Microsoft Excel. Instances of theatre over-running were identified, and these outliers were reviewed in more detail. Results: We identified two main time management issues in our department. The first occurs prior to the first procedure which highlighted significant delays with only one instance of KTS at 08:30 during the period of data collection. The second notable issue is the pattern of delays. There was a trend toward longer delays between cases as the day proceeds. Conclusions: Upon review of our data, we were able to identify possible areas of improvement in the time management of our theatre group. These improvements will allow for accurate theatre planning which should be a priority for all stakeholders given the significant waiting lists created by the COVID19 pandemic. There are many peer-reviewed methods of improving the efficiency of departments such as ours. Further work is required to discuss targets for improvement with relevant stakeholders and to implement PDSA cycles to assess the impact of implemented changes in our theatre.